Salam Adat of Wemale and Alune Tribes in Maluku - Wakano, Abidin; Lapele, Fitria; Prihono, Eko Wahyunanto; Ndayizeye, Oscar (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
Greetings serve as a means of expressing the identity of a region. Adat greetings have been preserved within tribes or small community groups, stemming from ancestors' lives in each area. The Wemale and Alune tribes hold significant positions and have played a crucial role in disseminating the Maluku language. This study aims to explore adat greetings through the lens of language structure. Employing a qualitative research methodology with an ethnographic approach, the research was conducted across eight sub-districts in the Western Seram Regency (SBB). Data collection techniques included observation, interviews, and Focus Group Discussions (FGD). The data were analyzed using the four phases of the Spradley Model, which encompasses descriptive, structural, and contrastive analysis, and thematic analysis to understand the nuances of language structure at both macro and micro levels. The findings revealed that the indigenous people of SBB possess at least 20 adat greetings. Eleven of these have been proposed as conventional greetings for official occasions, while six are recommended for use as conventional adat greetings during adat ceremonies or official events. These adat greetings are intended to signify a significant milestone in the renewal and sustainability of the languages of both tribes in a regenerative and sustainable manner.